Adjuvant chemotherapy after preoperative (chemo)radiotherapy and surgery for patients with rectal cancer: a systematic review and meta-analysis of individual patient data. Issue 2 (February 2015) - Breugom, Anne J; Swets, Marloes; Bosset, Jean-François; Collette, Laurence; Sainato, Aldo; Cionini, Luca; Glynne-Jones, Rob; Counsell, Nicholas; Bastiaannet, Esther; van den Broek, Colette B M; Liefers, Gerrit-Jan; Putter, Hein; et al.
Summary: Background: The role of adjuvant chemotherapy for patients with rectal cancer after preoperative (chemo)radiotherapy and surgery is uncertain. We did a meta-analysis of individual patient data to compare adjuvant chemotherapy with observation for patients with rectal cancer. Methods: We searched PubMed, Medline, Embase, Web of Science, the Cochrane Library, CENTRAL, and conference abstracts to identify European randomised, controlled, phase 3 trials comparing observation with adjuvant chemotherapy after preoperative (chemo)radiotherapy and surgery for patients with non-metastatic rectal cancer. The primary endpoint of interest was overall survival. Findings: We analysed data from four eligible trials, including data from 1196 patients with (y)pTNM stage II or III disease, who had an R0 resection, had a low anterior resection or an abdominoperineal resection, and had a tumour located within 15 cm of the anal verge. We found no significant differences in overall survival between patients who received adjuvant chemotherapy and those who underwent observation (hazard ratio [HR] 0·97, 95% CI 0·81–1·17; p=0·775); there were no significant differences in overall survival in subgroup analyses. Overall, adjuvant chemotherapy did not significantly improve disease-free survival (HR 0·91, 95% CI 0·77–1·07; p=0·230) or distant recurrences (0·94, 0·78–1·14; p=0·523) compared with observation. However, in subgroup analyses, patients with a tumour 10–15 cm from the anal verge had improved disease-free survival (0·59, 0·40–0·85; p=0·005, pinteraction =0·107) and fewer distant recurrences (0·61, 0·40–0·94; p=0·025, pinteraction =0·126) when treated with adjuvant chemotherapy compared with patients undergoing observation. Interpretation: Overall, adjuvant fluorouracil-based chemotherapy did not improve overall survival, disease-free survival, or distant recurrences. However, adjuvant chemotherapy might benefit patients with a tumour 10–15 cm from the anal verge in terms of disease-free survival and distant recurrence. Further studies of preoperative and postoperative treatment for this subgroup of patients are warranted. Funding: None.